TRANSFORMATION OF INDONESIAN RICE PRODUCTION: ANALYSIS OF GROWTH TRENDS AND MAIN DETERMINANT FACTORS FOR THE PERIOD 2003–2023 - Herdiana Anggrasari; Dhika Cahyasita (Universitas Veteran Bangun Nusantara, 2026)
This study analyzes the transformation and determinants of rice production in Indonesia for the period 2003–2023 using time series data and the Error Correction Model (ECM) method. Rice commodities face a dualism between government self-sufficiency efforts and structural defense, particularly land conversion that significantly reduces the national rice field area. The analysis results show that the rice production growth rate (CAGR) is very low. The positive growth that occurs is dominated by productivity increases, while the area of rice fields experiences contraction. Partially, the variable Harvested Paddy Area is proven to have the most significant and elastic influence on rice production, both in the long and short term, indicating that Harvested Area is the main determinant. The Labor variable shows a significant positive effect only in the long-term equilibrium, while UREA Fertilizer, Agricultural Credit, and Population are found to be statistically insignificant in affecting production individually. This sector also shows a rapid adjustment mechanism (negative and significant ECT) in responding to shocks. These findings confirm the crucial role of Harvested Area in production volume and provide empirical justification for land extensification policies. However, the desire for production demands an integrated strategy of extensification and intensification, supported by strict land protection regulations and improving the quality of the workforce, as a prerequisite for achieving sustainable growth. Keywords: Agricultural Development, Harvest Area, Regional Economy, Rice Production.